Friday

April 18, 2014

April 18, 2014

Posted by **Mary** on Friday, October 4, 2013 at 12:26pm.

-3x-y+2z = 7

2y+z= -5

3x+6y= -21

4

2

1

3

- Algebra -
**Mary**, Friday, October 4, 2013 at 12:37pmthx :)

- Algebra -
**Reiny**, Friday, October 4, 2013 at 12:41pmadd the 1st and 3rd

5y + 2z = -14

from the 2nd: z = -2y-5

plug into 5y + 2z = -14

5y + 2(-2y-5) = -14

y = -4

into the 3rd:

3x -24 = -21

3x =3**x = 1**

btw: z = 3

**Related Questions**

algebra - 3x + 4 > 9, with x = 2 determine whether or not the solution ...

adult education - How do you know if a value is a solution for an inequality? ...

Algebra - How do you know if a value is a solution for an inequality? How is ...

Algebra - How do you know if a value is a solution for an inequality? How is ...

Algebra - How do you know if a value is a solution for an inequality? How is ...

Algebra - How do you know if a value is a solution for an inequality? How is ...

Math (Algebra) - How do you know if a value is a solution for an inequality? How...

Algebra - How do you know if a value is a solution for an inequality? how is ...

algebra - How do you know if a value is a solution for an inequality? How is ...

algebra - How do you know if a value is a solution for an inequality and how is ...